How does Diglossia in Arabic affect the development of morphological knowledge throughout elementary schools? - Abu Dahud, Riham Mutlak-; Ibrahim, Raphiq; Shany, Michal (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
The current study aimed to examine the impact of linguistic distance between spoken Arabic vernacular (SAV) and modern standard Arabic (MSA) on the development of morphological knowledge in the standard Arabic language throughout elementary school. 132 native Arab children (67 boys and 65 girls) from 2nd, 4th and 6th grade have participated in four morphological tasks. The study's results indicated that a significant advantage is ascribed to morphology in spoken Arabic over standard Arabic. This advantage was found beyond the type of task and along the grades examined in the study. In addition, it was found that with the advance in the level of grade, the gaps between the spoken language and the standard language is reduced only at the level of production. Furthermore, the findings showed that throughout the second, fourth and sixth grades, there is a significant advantage for the performance at the identification level over the performance at the production level. A significant interaction was also found in the gap between identification to production and at the level of grade concerning the literary language. The psycholinguistic implications are discussed in light of previous findings regarding morphological knowledge, type of words (cognate versus noncognate) and recognition versus production processes.